Impatiens roingensis (Balsaminaceae): a new species from northeast India. Issue 2 (2nd July 2016) - Hareesh, V.S.; Joe, Alfred; Prashob, P.; Sabu, M.
Abstract : Impatiens roingensis from Arunachal Pradesh, northeast India, is described as new. A detailed description of the plants, their distribution and ecology along with colour photographs are provided for ease of identification.